Complementary and alternative medicine in the tretment of schizophrenia - Babić, Dragan, liječnik (Array, 2009)
Schizophrenia is a serious mental disorder. Due to synthesis of numerous high quality antipsychotic medications, a great progress in the treatment of it has been made during the last 50 years. The medicine gradually begins to understand that some of the alternatives used earlier in centuries are complementary methods that were unnecessarily suppressed and excluded from the treatment. On the other hand, a number of countries where this is legally possible is growing and there is also an increasing number of patients seeking alternative and complementary methods in the treatment of schizophrenia. The aim of this paper is to encourage and reflect upon the meaning of alternative and complementary methods in the treatment of schizophrenia as well as to try and prevent forgetting their meaning whenever it is justified and based on facts